A Case of Severe Hypercalcemia Causing Acute Kidney Injury: An Unusual Presentation of Acute Lymphoblastic Leukemia - Hye Sun Hyun; Peong Gang Park; Jae Choon Kim; Kyun Taek Hong; Hyoung Jin Kang; Kyung Duk Park; Hee Young Shin; Hee Gyung Kang; Il Soo Ha; Hae Il Cheong (Korean Society of Pediatric Nephrology, 2017)
Severe hypercalcemia is rarely encountered in children, even though serum calcium concentrations above 15-16 mg/dL could be life-threatening. We present a patient having severe hypercalcemia and azotemia. A 14-year-old boy with no significant past medical history was referred to our hospital with hypercalcemia and azotemia. Laboratory and imaging studies excluded hyperparathyroidism and solid tumor. Other laboratory findings including a peripheral blood profile were unremarkable. His hypercalcemia was not improved with massive hydration, diuretics, or even hemodialysis, but noticeably reversed with administration of calcitonin. A bone marrow biopsy performed to rule out the possibility of hematological malignancy revealed acute lymphoblastic leukemia. His hypercalcemia and azotemia resolved shortly after initiation of induction chemotherapy. Results in this patient indicate that a hematological malignancy could present with severe hypercalcemia even though blast cells have not appeared in the peripheral blood. Therefore, extensive evaluation to determine the cause of hypercalcemia is necessary. Additionally, appropriate treatment, viz., hydration or administration of calcitonin is important to prevent complications of severe hypercalcemia, including renal failure and nephrocalcinosis.